PERKEMBANGAN SOSIOEMOSIONAL ANAK USIA DINI - Sapendi Sapendi (AT-TURATS, 2008)
Understanding child development is crucial, especially for parents and teachers. With a good understanding, parents and teachers can properly treat a child. While many authors give attention to child’s development of cognition and mental intelligence, this paper focuses on child’s development of social intelligence known as socio-emotional development. The author presents academic explanations of these themes based on three theoretical perspective i.e., Sigmund Freud’s theory of psychoanalysis, Erik Erikson’s theory and Bandura’s theory. Based on the theoretical study, the author concludes that emotional intelligence is a skill that is formed (constructed) by external factors such as parents, teachers and the environment. Therefore, it is important to have an appropriate strategy in interfering with socio-emotional development of children, so they can adapt to and act appropriately in their social environment.